2008
DOI: 10.1095/biolreprod.108.070540
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Oscillations During the Estrous Cycle Influence the Morphophysiology of the Gerbil (Meriones unguiculatus) Female Prostate (Skene Paraurethral Glands)1

Abstract: The hormonal oscillations that occur during the female reproductive cycle influence the morphophysiology of several organs of the reproductive system. The female prostate is a functional organ sensitive to the action of steroidal hormones, but it is not known whether the hormonal oscillations that occur during the reproductive cycle can alter the biology of this gland. Thus, the present work aims to evaluate the morphofunctional aspects of the female prostate during the gerbil estrous cycle. For this purpose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 20 publications
1
39
1
2
Order By: Relevance
“…This difference may be caused by the difference in ovulation time. Contrary to the results of this study, other work has indicated that serum E2 reaches a peak at diestrus while serum P4 peaks at estrus in Mongolian gerbils [6]. although the measurement method used was the same, the standard error of E2 and P4 peak values high, and it was not stated whether or not the female gerbils were virgins.…”
Section: Hormonal Variations During the Estrous Cycle In Virgin Mongocontrasting
confidence: 99%
See 1 more Smart Citation
“…This difference may be caused by the difference in ovulation time. Contrary to the results of this study, other work has indicated that serum E2 reaches a peak at diestrus while serum P4 peaks at estrus in Mongolian gerbils [6]. although the measurement method used was the same, the standard error of E2 and P4 peak values high, and it was not stated whether or not the female gerbils were virgins.…”
Section: Hormonal Variations During the Estrous Cycle In Virgin Mongocontrasting
confidence: 99%
“…We can further understand the reproductive characteristics of Mongolian gerbils through studies -Original-of reproductive hormones. However, there are only a few reports on the secretion patterns of reproductive hormones during different reproductive states in Mongolian gerbils [6,11,12,22,24]. The aims of this study were, first, to confirm the variations of serum estradiol (E2) and progesterone (P4) levels in different reproductive states of Mongolian gerbils and to analyze the differences of E2 and P4 patterns between Mongolian gerbils and other rodents such as rats and mice; second, to analyze the differences in variations of E2 and P4 levels in primiparous and multiparous gerbils; and third, to analyze the relationships between the two hormone levels and the reproductive states of Mongolian gerbils.…”
Section: Introductionmentioning
confidence: 99%
“…1). Earlier studies have reported detectable PSA in 50 % non pregnant females [2,15,23]. Filella et al [16] used ultrasensitive Fluoro-immunometric assay (detection limit of 0.004 lg/l) detected the presence of PSA in 58 % of the sera tested.…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings were reported by Zarghami et al [11] who found highest PSA concentrations during mid to late follicular phase and a difference of 10-12 days between PSA and progesterone peak. Studies in other mammals have also indicated that PSA secretion is higher in follicular phase and the authors opined that these cyclical changes in PSA are probably determined by cyclic variations in estradiol and progesterone [23].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported the changes in the levels of estradiol and progesterone during the different reproductive states in Mongolian gerbils [15]. However, data on the secretion patterns of reproductive hormones in Mongolian gerbils during different reproductive states remain insufficient [4,9,10,25,27]. To our knowledge, this is the first study of the secretion patterns of gonadotropin and prolactin during consecutive reproductive states in Mongolian gerbils, and it therefore contributes to a detailed understanding of their reproductive physiology.…”
Section: Introductionmentioning
confidence: 90%